Comparison between the influence of roxadustat and recombinant human erythropoietin treatment on blood pressure and cardio-cerebrovascular complications in patients undergoing peritoneal dialysis - Cheng, Shuiqin; Zhou, Tingting; Yu, Le; Zhang, Zhihong; Chen, Yunmin; Zhang, Man; Cui, Jingjing; Yu, Wenxin; Zhou, Jian; Yu, Yusheng (Frontiers in Medicine, 2023)
Introduction Roxadustat treatment in PD patients is equivalent to ESAs in increasing hemoglobin (Hb). But blood pressure, cardiovascular parameters, cardio-cerebrovascular complications and prognosis in the two groups before and after treatment has not been sufficiently discussed. Methods Sixty PD patients who were treated with roxadustat for renal anemia in our PD center recruited from June 2019 to April 2020 as roxadustat group. PD patients treated with rHuEPO were enrolled at a 1:1 ratio as rHuEPO group using the method of propensity score matching. Hb, blood pressure, cardiovascular parameters, cardio-cerebrovascular complications and prognosis were compared between the two group. All patients were followed up for at least 24 months. Results There were no significant differences in baseline clinical data or laboratory values between roxadustat group and rHuEPO group. After 24 months of follow-up, there was no significant difference in Hb levels (p > 0.05). There were no significant changes in blood pressure, or the incidence of nocturnal hypertension before and after treatment in roxadustat group (p > 0.05), while blood pressure significantly increased in rHuEPO group after treatment (p < 0.05). Compared with roxadustat group after follow-up, rHuEPO group had a higher incidence of hypertension, the levels of cardiovascular parameters were worse and cardio-cerebrovascular complications had a higher incidence (p < 0.05). Cox regression analysis showed age, systolic blood pressure, fasting blood glucose, and rHuEPO use before baseline were risk factors for cardio-cerebrovascular complications in PD patients, while treatment with roxadustat was a protective factor for cardiovascular and cerebrovascular complications. Conclusion Compared with rHuEPO, roxadustat had less influence on blood pressure or cardiovascular parameters, and it was associated with a lower risk of cardio-cerebrovascular complications in patients undergoing PD. Roxadustat has a cardio-cerebrovascular protective advantage in PD patients with renal anemia.